Herramienta CASE para graficar y documentar diagramas UML 2.2 - Uriol More, Diana Elizabeth (2012)
This paper shows the development of a CASE tool for UML 2.2 diagrams graph, which we will call Lenny UML 1.0. This tool was built to the need for various companies, which acquire a tool like this is very expensive for the payment of licenses and often find it difficult to handle them or understand them, either by their unfriendly interfaces or the language in which they are located._x000D_ LennyUML is designed for all companies regardless of Peruvian area, allowing them to document their systems with diagrams commonly used in our area such as: Use Case diagram, object diagram, class diagram, state diagrams and activity diagrams. This tool serves as a focus for future updates and / or changes that may occur in the system as per the changing and dynamic nature of software development prevents a system can be fully defined in the specification phase or continuing changes The Subsequent phases are reflected in the documentation._x000D_ For the development of this free tool for future users have used the programming language Java 1.6 in Eclipse IDE own different libraries for drawing UML artifacts._x000D_ It is noteworthy that this thesis is to implement a new tool, based on what we currently provides the technology and trying to adapt to the Peruvian market. Therefore inviting prospective partners to continue it, adding many more features required by enterprises of our country._x000D_ Chapter 1 gives an overview of the project, the problem to solve and justification of the thesis. Chapter 2 discusses the Unified Modeling Language, an introduction to this, its evolution, and diagrams that were used for this thesis. Chapter 3 shows CASE tools, evolution, components and features they have. Chapter 4 describes the development of the tool, the methodology and design of our software to the results obtained after completion of the project._x000D_ Finally, we report the results and future work